PENGARUH HUTANG, UKURAN PERUSAHAAN, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP PERTUMBUHAN LABA PADA PT DELTA ATLANTIC INDAH MEDAN PERIODE 2013 - 2017 - SHILA ATIKA; WILLIAM .; NIRWANA DEWI HARAHAP; SALEH SITOMPUL (JURNAL ILMIAH KOHESI, 2019)
This research was conducted PT. Delta Atlantic Indah Medan. The main purpose of this research is to acknowledge and toanalyze the impact of debts, the size of the company, the structure of the capital and liquidation towards the growth profit ofPT Delta Atlantic Indah Medan period 2013-2017. The methods used on this research are descriptive analyze method todescribe the collected data without means to make a general conclusion. Data analyze method used are multiple linearregression provided in SPSS software. The result shows debts, the size of the company, the structure of the capital andliquidation simultaneously has a positive impact and significant on the growth profit of PT Delta Atlantic Indah Medan period2013-2017. In the determination coefficient the value of adjusted R2 obtained 12,4%, meaning that the variable variation ofdebts, size of the company, the structure of the company and liquidation while the rest of 87,6% was not described in thisresearch, such as cash flow, capital, interest rate, tax, credits, operational expenses and profit. Debt, Size of the company,Structure of the capital in partial did not positively affected and significant to profit growth of PT Delta Atlantic Indah Medanperiod 2013-2017. Liquidation partially has positive impact and significant on the profit growth of PT Delta Atlantic IndahMedan period 2013-2017.